Gender mainstreaming in Preventing and Countering Violent Extremism - Hanna Wdzięczak (Journal for Deradicalization, 2022)
How does gender identity factor into preventing violent extremism, and rehabilitating individuals involved with terrorist networks? This question is becoming increasingly visible in the literature on preventing and countering violent extremism (P/CVE) programs. However, it remains unclear how experts working on P/CVE initiatives understand the importance of gender in the context of violent extremism, and how they integrate gender-sensitive approaches in their work. By relying on the concept of gender mainstreaming, this paper aims to explore how much knowledge and understanding of gender perspectives in terrorism and violent extremism P/CVE practitioners have. Based on 10 interviews with 11 experts working on P/CVE programs, this study reveals that formal knowledge about gender perspectives in violent extremism remains relatively limited among P/CVE practitioners. On one hand, most experts intuitively realize how gender identity influences one’s participation in, and disengagement from violent extremism. Most P/CVE practitioners also recognize the need for gender equality in planning and executing their programs. However, the interviews revealed that there remain several areas of improvement. Firstly, although the interviewed P/CVE practitioners appreciate the importance of having a gender-sensitive perspective, they are not sure how these insights can help build more effective P/CVE mechanisms. Moreover, some of the P/CVE experts remain unclear on what terminology should be used to describe gender-sensitive P/CVE work. This paper argues that there is a need for greater dialogue between global security organizations, academics, and the P/CVE practitioners working on the ground, to design more effective and community-oriented preventing and countering violent extremism programs.